Impact of target‐mediated drug disposition on hetrombopag pharmacokinetics and pharmacodynamics in Chinese healthy subjects and patients with chronic idiopathic thrombocytopenic purpura - Wang, Zhenlei; Zeng, Zhijun; Ye, Lijun; Zhu, Xiaohong; Pei, Yuwen; Wang, Yongsheng; Zheng, Li (British journal of clinical pharmacology, 2022)
Aims The pharmacokinetics (PK) of hetrombopag were found to be nonlinear across evaluated dose ranges. The aim of this study was to develop a mechanism‐based population pharmacokinetic/pharmacodynamic (PopPK/PD) model and to provide a reasonable expected therapeutic dose for a future confirmatory clinical study of hetrombopag. Methods Nonlinear mixed‐effects modelling was performed using pooled 2168 hetrombopag concentrations and 1526 platelet counts from 72 healthy subjects and 32 chronic idiopathic thrombocytopenic purpura (ITP) patients from two phase I studies and one phase II study. The final model was evaluated via goodness‐of‐fit plots, visual predictive check and nonparametric bootstrap. Simulations from the validated PopPK/PD model were used to devise an expected therapeutic dose for later confirmatory clinical study. Results The pharmacokinetic data of hetrombopag were well described by a modified target‐mediated drug disposition (TMDD) model with dual sequential first‐order absorption. Mean parameter estimates (interindividual variability) were CL/F 7.66 L/h (63.5%), Vc/F 30.0 L (77.2%) and Kdeg 0.693/h (87.1%). The pharmacodynamic profile was well described by a five‐compartment lifespan model with four‐transit and one‐platelet compartments. Simulation results suggested that chronic ITP patients following 10 mg once‐daily hetrombopag would able to achieve an ideal platelet count level (50‐200 × 109/L). Conclusion TMDD was the primary reason leading to nonlinear PK profile of hetrombopag. Our PK/PD modelling and simulation results support 10 mg once‐daily as the recommended therapeutic dose for chronic ITP patients in subsequent confirmatory clinical study of hetrombopag.